Effects of N6-Methyladenosine Modification on Cancer Progression: Molecular Mechanisms and Cancer Therapy - Zhu, Yong-fu; Wang, Shu-Jie; Zhou, Jie; Sun, Ye-han; Chen, You-mou; Ma, Jia; Huo, Xing-xing; Song, Hang (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) is a major internal epigenetic modification in eukaryotic mRNA, which is dynamic and reversible. m6A is regulated by methylases ("writers") and demethylases ("erasers") and is recognized and processed by m6A-binding proteins ("readers"), which further regulate RNA transport, localization, translation, and degradation. It plays a role in promoting or suppressing tumors and has the potential to become a therapeutic target for malignant tumors. In this review, we focus on the mutual regulation of m6A and coding and non-coding RNAs and introduce the molecular mechanism of m6A methylation involved in regulation and its role in cancer treatment by taking common female malignant tumors as an example.